The Arguments for a Permanent Zero Interest Rate. - Musgrave, Ralph Stephen (Advances in Social Sciences Research Journal, 2018)
A zero interest rate regime is one where government issues a form of money which pays no interest, but does not borrow. There are three reasons for that policy. First, most if not all the reasons given for government borrowing are hopeless. Second, adjusting interest rates is a policy which is riddled for anomalies. E.g. in order to be able to cut interest rates, government first has to artificially raise them. But artificial adjustments to the price of anything, including the price of borrowed money does not make economic sense. Third, the market failure which causes recessions is not the failure of interest rates to fall. It’s the failure of wages and prices to fall, which would increase the real value of base money and government debt (if there is any), which in turn would encourage spending. That’s the “Pigou effect”. If government and central bank were simply to create new base money and spend it (and/or cut taxes) in a recession, that would come to much the same as the Pigou effect. That is what might be called a “free market compliant” policy. Interest rate adjustments are not “compliant”. Thus government should not borrow other than for very good reasons, if there are any, and artificial adjustments to interest rates should cease, except perhaps in emergencies. That, for want of a better phrase, can be described as a “permanent zero interest rate” policy. That policy is not far from the UK Labour Party’s new fiscal rule.